The Nutraceutical Potential of Blackcurrant (Ribes nigrum) for Glycemic Control and Metabolic Health: Mechanistic and Translational Insights - Piotr Religa; Magdalena D. Pieczynska-Kovacs; Marzena Łazarczyk; Bhupinder Kapoor; Rajan Logesh; Smith B. Babiaka; Piotr Poznański; Michel-Edwar Mickael; Ricardo Lagoa; Mariusz Sacharczuk; Ibrahim F. Rehan; Asmaa Elnagar; et al. (Nutrients, 2026)
Diabetes mellitus is a pervasive global health crisis, with type 2 diabetes (T2D) representing the majority of cases. While conventional pharmacological therapies exist, suboptimal efficacy, adverse effects, and inadequate glycemic control in a substantial proportion of patients highlight the need for complementary strategies. There is growing scientific and clinical interest in plant-based functional foods, including Ribes nigrum L. (blackcurrant), which is rich in bioactive phytochemicals such as anthocyanins, flavonols, and phenolic acids. This review evaluates the antidiabetic and metabolic regulatory potential of blackcurrant, focusing on its multi-target mechanisms of action. Available experimental evidence suggests that blackcurrants may influence glucose metabolism through several mechanisms, including inhibition of carbohydrate-digesting enzymes (α-amylase and α-glucosidase), modulation of intestinal glucose transporters (SGLT1 and GLUT2), and potential modulation of insulin sensitivity involving AMPK signaling and GLUT4 translocation. In addition, blackcurrant constituents may stimulate glucagon-like peptide-1 (GLP-1) secretion, modulate gut microbiota composition, and exert antioxidant and anti-inflammatory effects that counteract key drivers of insulin resistance and β-cell dysfunction. Supporting human studies indicate that blackcurrant consumption has been associated with attenuation of postprandial glycemic and insulinemic responses and modest improvements in cardiometabolic biomarkers, although findings remain limited by study size, duration, and formulation heterogeneity. Overall, Ribes nigrum represents a promising dietary adjunct for the prevention and management of T2D through multi-target metabolic regulation.